An introduction to political science - Jacobsohn, John A. (Belmont, Calif. West/Wadsworth, 1998)
this book emphasizes the relationship between the society and the state, rather than between the individual and the state ... [It] draws on as much cross-cultural and even historical information as possible. -Pref.
Keywords: Political science